Psychometric analysis of the self-reporting questionnaire (SRQ-29) among university students - Qatrunnada, Rizqi Zulfa; Bayu Suseno; Muhammad Yazid (Jurnal Ilmiah Psikologi Terapan, 2025)
The SRQ-29 is a measurement tool developed by WHO for the early detection of mental health problems. However, no research has focused on the psychometric testing of the SRQ-29 instrument. This study aimed to investigate the psychometric properties of the Indonesian version of the Self-Reporting Questionnaire (SRQ-29) as a screening tool for the early detection of mental health problems in individuals who are university students. The original version of the scale was adapted and translated into Indonesian and tested for validity, reliability, and factor analysis among university students. The adaptation process followed the guidelines of the International Test Commission and included translation, expert review, cognitive interview, and psychometric evaluation. The participants who actively participated in this study were 323 students from various faculties of Universitas Muhammadiyah Surakarta (UMS), selected using a convenience sampling technique. Data analysis to test content validity using Aiken's V analysis, construct validity using item factor analysis (IFA), and test reliability using Cronbach alpha. In general, the results showed that the measurement instrument has good validity and reliability, so it can be used in the population of university students in Indonesia to screen their mental health status.